2023
DOI: 10.1128/spectrum.01943-22
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of One or More Cellular Aurora Kinases Impair the Replication of Herpes Simplex Virus 1 and Other DNA and RNA Viruses with Diverse Genomes and Life Cycles

Abstract: We have demonstrated that aurora kinases play a role during HSV-1 lytic infection. Three aurora kinase inhibitors significantly impaired HSV-1 immediate-early gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In both these cases, there was no evidence of AurA-HDAC6 pathway involvement, or that primary cilia loss was beneficial to the microbe. AurA kinase activity has not been linked with bacterial infection, but appears to promote replication of several viruses [ 42 , 43 ]. In addition, the E6 ligase of human papillomavirus (HPV) interacts with AurA to promote HPV-mediated carcinogenesis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In both these cases, there was no evidence of AurA-HDAC6 pathway involvement, or that primary cilia loss was beneficial to the microbe. AurA kinase activity has not been linked with bacterial infection, but appears to promote replication of several viruses [ 42 , 43 ]. In addition, the E6 ligase of human papillomavirus (HPV) interacts with AurA to promote HPV-mediated carcinogenesis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…(iv) PHA-793887: Few experimental studies have been conducted to certify its activity, but it was demonstrated in vitro that PHA-793887 was able to interfere with the viability of osteosarcoma cells [76]. (v) JNJ-7706621: a potent inhibitor of CDKs and Aurora kinase (AURKA) demonstrated effectiveness in dealing with the herpes simplex virus 1 [77].…”
Section: Discussionmentioning
confidence: 99%
“…RNA was isolated according to manufacturer’s protocol and reverse transcribed as published (ref). cDNAs of viral and cellular transcripts were amplified using primers for ICP0, ICP4, ICP27, and 18S rRNA as previously described (36).…”
Section: Methodsmentioning
confidence: 99%